Studi Penggunaan Media Sosial sebagai Wadah Penyelenggaraan Demokrasi oleh Mahasiswa Institut Teknologi Bandung - Bilqis Naura Safira Rizam Rizam; Ar Ryan Shifa Izzati; Chrisella Naomi; Antonius Hansel Kartagunawan (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2022)
Active users of social media are young people aged 18-29 years. Part of the community included in this group are college students. College students use social media to obtain and disseminate informations. Occasionally, social media is used to convey political opinions on campus or country issues. Therefore, this study was conducted to determine the use and the effectiveness of social media in voicing internal and national issues by college students. The subjects of this study were students of the Bandung Institute of Technology (ITB) who are active members of the Kabinet Keluarga Mahasiswa (KM), Himpunan Mahasiswa Jurusan (HMJ), and Unit Kegiatan Mahasiswa (UKM). The research was conducted using qualitative methods and data obtained by survey methods and literature study. This study aims to determine the role and effectiveness of social media in implementing democracy and optimizing its use. This study is the first to examine the use of social media in democratic practices by Indonesian college students. Therefore, this research is expected to provide an overview of the use of social media by college students as well as ways to increase the effectiveness of their use.